Using Communications Theory to Explore Emergent Organisation in Pagan Culture - Coco, Angela (Australian religion studies review, 2011)
Pagan culture presents a paradoxical case to the traditional frameworks and methodologies social scientists have used to describe religious organisation. A key factor influencing Paganism's emergence has been its adoption of online communications. Such communications provide a means of coordinating activities in and between networks accommodating diverse beliefs and practices and the ability to avoid overarching hierarchical organisation. These characteristics have led theorists to label Paganism as a postmodern religion, signalling the possibility of a different kind of social organisation from that evidenced in modern religions. Karaflogka (2003) distinguishes between two aspects of the move online, religion in cyberspace and religion on the Internet. While the Internet may be an online place for cybercovens and for performing cyber rituals, the analysis in this paper focuses on the interweaving of online and offline communicative practices. I suggest that communications theories, as outlined in Wenger's communities of practice' model (1998) and Taylor and Van Every's (2000) communications mapping, afford frameworks for exploring the inter-connectedness of online/offline interactions and a means of identifying emergent organisation in the Pagan movement. The analysis focuses on a particular feature of Pagan organisation, the accommodation of both group-oriented and solitary pagans.